Long‐term clinical outcomes of biliary cast syndrome in liver transplant recipients. Issue 3 (11th March 2013) - Paik, Woo Hyun; Lee, Sang Hyub; Ryu, Ji Kon; Song, Byeong Jun; Kim, Jaihwan; Kim, Yong‐Tae; Yoon, Yong Bum
<x xml:space="preserve">Abstract</x> Biliary cast syndrome (BCS) is an uncommon complication of orthotopic liver transplantation (OLT), so the long‐term treatment outcomes of BCS are not well characterized. The purpose of this study was to evaluate the long‐term treatment outcomes and prognosis of BCS after OLT. The medical records of 1097 patients who underwent OLT from January 2000 to September 2009 were reviewed. Those patients who had BCS were evaluated with respect to the treatment method, overall survival and relapse rates, and relapse‐free time. Twenty‐three patients (2.1%) were diagnosed with BCS with a mean overall follow‐up of 59.9 months. All the patients had benign biliary strictures and repeatedly underwent balloon dilatation by an endoscopic or percutaneous approach. Primary biliary cast removal was tried with the endoscopic method from 11 patients and with the percutaneous methods from 12 patients. Casts were completely removed by repetitive procedures in 22 patients, but BCS relapsed in 12 patients (55%). Persistent biliary strictures were significantly associated with the BCS relapse frequency (0.37 versus 0.05 times per year, P = 0.006). The 5‐year overall survival rate for BCS patients after OLT was 87%. The risk factors associated with early relapse were female sex, hepatic artery stenosis, and acute cellular rejection. In a multivariate analysis, acute cellular rejection was the only significant risk factor for early relapse (hazard ratio = 11.1, 95% confidence interval = 1.9‐63.2, P = 0.007). In conclusion, patients with BCS frequently relapse, and multiple interventions and the treatment of biliary strictures are needed. Acute cellular rejection after OLT is a significant risk factor for early relapse. Liver Transpl 19:275–282, 2013. © 2013 AASLD.